Canva, Keterampilan Berbicara, Partisipasi Siswa, Teks Prosedur - Hawa, Hawa; Hersulastuti; Endang Eko Djati (Universitas Muhammadiyah Sorong, 2025)
This study investigates the use of Canva as a digital learning tool to improve students' speaking skills and active participation in delivering procedural texts. This study specifically aims to: analyze How the application of Canva in learning can improve students' speaking skills in procedural texts; and explore How Canva can improve students' active participation in speaking in front of the class when delivering procedural texts. Conducted using the Classroom Action Research method. This study involved 32 grade IX students at SMPN 3 Sorong Regency and was carried out in two cycles, each consisting of planning, action, observation, and reflection stages. Data were collected through speaking performance assessments (pre-test and post-test), observation sheets, participation rubrics, questionnaires, and documentation, and analyzed using quantitative and qualitative descriptive methods. The findings show that; 1) Canva can improve students' speaking skills, with an average score increasing from 61.7 in the pre-test to 79.2 in the second cycle post-test; 2) Canva increases student engagement in class, making them more confident, expressive, and enthusiastic in speaking presentations. Canva's creative and visual features contribute to reducing anxiety and encouraging an interactive learning environment. These results indicate that Canva is an effective educational tool to improve English language skills and encourage student participation. This study also highlights that the use of visual media such as Canva can accommodate various learning styles of students. The integration of technology in language learning has been shown to provide a more meaningful and interesting learning experience. Teachers also feel helped in presenting materials more systematically and contextually. Increasing student learning motivation is another positive impact of using Canva. With strong visual support, students find it easier to understand the structure and sequence in procedural texts. This shows that a digital media-based approach is able to bridge the gap between theory and practice in speaking learning. The implications of this study can be a reference for teachers in designing innovative technology-based learning strategies.